(untitled) (Scientific journal of the Fergana State University, 2023)
In this article it is told about Usmon Huzha Pulatkhuzhayeva the period from the last quarter of the 19th century to the 60th years of the 20th century fighting for independence of Uzbekistan (Turkestan) the research sources.